Portrait of a Religious Fanatic - Horace Bristol:::Creator::::::::::::
Portrait of a Religious Fanatic.' Horace Bristol was an American Photojournalist who travelled with Steinbeck in 1938 and documented the migrant families. Bristol used the characters from Steinbeck's novel to title his photographs and Twentieth Century Fox used his photographs to assist in the casting of The Grapes of Wrath. RESTRICTED USE